2021
DOI: 10.3389/fmed.2021.626909
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of the Trace Elements Zinc and Magnesium With Diabetic Nephropathy-Associated Renal Functional Damage in Patients With Type 2 Diabetes Mellitus

Abstract: Zinc (Zn) and magnesium (Mg) are essential trace elements in humans. Their deficiency may be associated with inflammation and oxidative stress (OS) in patients with diabetic nephropathy (DN), but the mechanisms involved have not been fully characterized. We aimed to investigate the relationships between circulating concentrations of Zn and Mg and pro-inflammatory factors with DN-associated renal functional damage in patients with type 2 diabetes mellitus (T2DM). To this end, we studied 20 healthy people, 24 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Similarly, Makhlouph et al [19] showed a substantial difference in blood Zn levels among individuals with macro and microalbuminuria, with microalbuminuria patients having significantly higher serum Zn concentrations than patients with macroalbuminuria. According to our study findings, Zn serum levels were greater in microalbuminuria group contrasted to the macroalbuminuria group which was in coherence with the results found by Feng et al [20] discovered that the concentration of serum Zn was considerably lower in individuals with macroalbuminuria or renal failure than it was in those with microalbuminuria. Additionally, a negative correlation was existed among 24-hour urine albumin loss and serum Zn content in individuals with DN.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Makhlouph et al [19] showed a substantial difference in blood Zn levels among individuals with macro and microalbuminuria, with microalbuminuria patients having significantly higher serum Zn concentrations than patients with macroalbuminuria. According to our study findings, Zn serum levels were greater in microalbuminuria group contrasted to the macroalbuminuria group which was in coherence with the results found by Feng et al [20] discovered that the concentration of serum Zn was considerably lower in individuals with macroalbuminuria or renal failure than it was in those with microalbuminuria. Additionally, a negative correlation was existed among 24-hour urine albumin loss and serum Zn content in individuals with DN.…”
Section: Discussionsupporting
confidence: 92%
“…Addition of extra zinc to the culture medium of HepG2 cells transfected with the promoter of the Glo1 gene was associated with doubling of promoter activity [ 26 ]. This finding may well be pertinent to the clinical literature correlating lower plasma zinc levels in diabetics with increased risk for diabetic complications, including nephropathy, retinopathy, neuropathy, and cataracts [ 30 , 31 , 32 , 33 , 34 , 35 ]. These findings, however, should be viewed circumspectly inasmuch as hyperglycemia impairs renal retention of zinc; diabetics therefore tend to be relatively zinc deficient, and lower zinc status in diabetics may thus be a marker for poorer diabetic control [ 36 , 37 ].…”
Section: Nutraceutical Induction Of Glyoxalase 1 Expressionmentioning
confidence: 80%
“…Studies have been investigating potential therapeutic ways to slow the progression of DN and improve patient outcomes for many years [ 5 ]. Magnesium, an important mineral involved in many physiological processes, has attracted considerable attention recently because of its potential protective function in the development and progression of DN [ 6 ]. Magnesium supplementation has been linked to improved outcomes in animal and clinical research for the treatment of diabetes and its complications [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%